Plasmodium falciparum transcription in different clinical presentations of malaria associates with circulation time of infected erythrocytes - Richard Thomson-Luque (Nature Portfolio, 2021)
To understand malaria symptoms, several studies investigate association between parasite’s transcriptome and disease severity. Here, Thomson-Luque et al. reanalyze available transcriptomic data of P. falciparum and find that longer circulation of infected erythrocytes without sequestering to endothelial cells associates with decreasing parasitaemia and less severe disease.